Lessons from developing district-level M&E plans to implement the National Resilience Strategy - Kayamba-Phiri, Fundi (International Food Policy Research Institute, 2023)
The National Resilience Strategy (NRS) aims to build resilience against economic and environmental shocks, promoting inclusive growth, food security, and well-being for all Malawians. The NRS consists of four pillars: (1) Resilient Agricultural Growth; (2) Risk Reduction, Flood Control and Early Warning and Response Systems; (3) Human Capacity, Livelihoods, and Social Protection; and (4) Catchment Protection and Management. Titukulane RFSA is piloting the NRS in Zomba and Mangochi districts, working with District Councils to coordinate implementation with various stakeholders. This learning brief highlights the lessons learned from developing the Monitoring and Evaluation (M&E) plans in Zomba and Mangochi districts and offers recommendations for other districts planning to implement the National Resilience Strategy (NRS). The brief also discusses the Opportunities for Collaboration between National and District Pillar Leads and Aligning the NRS with Key Government Strategies, particularly the Malawi 2063 (MW 2063), to foster synergy and impact.